DRONE LAST MILE DELIVERY: AN ASSESSMENT OF THE VIABLE MARKET AND SECURITY POTENTIAL OF DRONE DELIVERY (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: the paper includes a review of the literature in the field of drones, drone technology, possible implementation in the field of the last mile concept, legislation, suitability of technology in the field of security, weather conditions, social acceptance and later focuses on checking the possible implementation of drones according to the set parameters.Methodology: for the purposes of research and obtaining answers to the posed research question and hypotheses, we used the method of literature review in the selected field, panel data analysis, conducted interviews with experts in the field of delivery drones in the Republic of Slovenia, and conducted secondary research.Results: the results show an assessment of the possible implementation of drones based on the analysis of the obtained data and interviews. We determined a realistic assessment of the potential of delivery drones, in which we included several vital aspects necessary for implementation.Conclusion: it was found that the current technology is not yet fully adequate, and significant technological improvements are also needed. It is also necessary to plan integrated urban spatial solutions that will enable safe and efficient delivery in the supply chain. Namely, delivery with drones is currently ineffective due to flight safety, harmful sound emissions and the inability to fly in bad weather conditions. Based on a literature review and a survey among large logistics companies, it was found that there are still many barriers to implementation due to legal norms and regulations, which are currently very constructive. It is unlikely, however, that parcel delivery will take off in an urban environment soon, as there are still many unknowns. With proper planning and use of suburban consolidation centres, e-vans, e-cars and bicycles are currently economically viable for last mile delivery.